The effects of eucalypt plantations on plant litter decomposition and macroinvertebrate communities in Iberian streams - Ferreira, Verónica (2015)
Eucalypt plantations cover over 1.5 million ha in the Iberian Peninsula. The effects of the replacement of native deciduous forests by exotic plantations on stream communities and litter decomposition, a key ecosystem process in forest streams, are poorly understood. We compared microbially driven and total (microbes + invertebrates) decomposition of alder and oak leaf litter (high and low quality resource, respectively) as well as macroinvertebrate communities associated with decomposing litter and in the benthos, in five streams flowing through native deciduous broad-leaved forests and five streams flowing through eucalypt plantations in central Portugal and northern Spain (20 streams total). Total decomposition rate of alder leaf litter was slower in eucalypt than in deciduous streams, which was attributed to lower macroinvertebrate (and also shredder) colonization. No major effects of eucalypt plantations were found on macroinvertebrate colonization and total decomposition of oak litter, likely due to the low contribution of invertebrates to the decomposition of nutrient-poor litter. Microbially driven litter decomposition was generally not affected by forest change, likely due to high functional redundancy among microbes. Eucalypt streams had fewer invertebrates in Portugal than in Spain, which might be attributed to summer droughts in Portugal and the absence of deciduous riparian corridors in eucalypt plantations. In northern Spain, the relatively wet climate allows streams to flow year-round and eucalypt plantations have riparian deciduous trees that mitigate the effects of plantations. This study highlights the need to consider regional differences in climate, native vegetation, and the importance of macroinvertebrates, when assessing the effects of plantations on stream ecosystem processes such as carbon cycling. It also suggests that preservation of native riparian corridors, especially in drier areas, where the native vegetation provides high quality litter to the streams, and where invertebrates play an important role in aquatic processes, may mitigate the effects of plantations on stream communities and processes.